A Ajaran Panca Sraddha Dalam Susastra Upanisad Sebagai Penguat Keyakinan Umat Hindu Di Era Globalisasi - Kadek Oka Prima Arta (Jurnal Pendidikan Agama, 2022)
The writing of this paper aims to explain the importance of Upanisad teachings as reinforcement of sraddha (belief) of Hindus in facing the era of globalization. As for the background of this writing, because now we have entered the era of globalization, the impact of this era of globalization brings very significant changes in social life, both positive and negative changes. No exception Hindus are also exposed to and experience these changes as a result of the era of globalization. Today's development influences various aspects of the life of Hindus starting from culture, ethics, morals, social, etc. both positive and negative. The occurrence of changes in Hindu society, especially negative changes as a result of the development of the era can not be separated from the beginning of the weakening of Sraddha or the belief of Hindus namely Panca Sraddha which is the basis of religious beliefs of Hindus, Panca Sarddha is the five basic beliefs of Hinduism the existence of God, belief in the existence of Atman who supports every creature, belief in the existence of karmaphala or the law of cause and effect, belief in the existence of punarbawa or reincarnation and belief in the existence of moksa or the highest freedom of Atman's union with Brahman. Upanisad is one of the sacred Hindu literature which has an important role as a reinforcer of Hindu sraddha, especially in this era of globalization because the Uprising Scriptures contain the highest discourse about secrecy on humanity, the Upanishad books contain the essence of the Vedas and are the basis of spiritual truth for people who are looking for spiritual enlightenment. No exception the Panca Sraddha teachings are also explained in the Upanishads, the teachings in the Upanishads are very useful for Hindus in navigating life, especially in facing the era of globalization which is as a guide and reinforcer of sraddha Hindus in order to control themselves and not affected by the development of a negative era. So that we are able to control ourselves and follow the developments in a positive way that does not conflict with religious teachings, by realizing and strengthening Panca Sraddha's teachings in self will automatically shape the morals, ethics and behavior of the ummah to be good. keywords: Upanishad, Sraddha, Globalization Era.